The effects of an 18-week training programme on movement economy of a long-distance runner - a case study - Zajac, B.; Mirek, W.; Ambrozy, T. (Journal of Kinesiology and Exercise Sciences, 2020)
Study aim: The aim of the work was to determine the effects of an 18-week training programme on the economics of running at a speed corresponding to the lactate threshold of an athlete from the track-and-field section of AZS AWF (University of Physical Education) Kraków. In addition, the objective was to determine the average heart rate and speed during a 10-km during in relation to threshold values for these parameters. Materials and methods: In the study, heart rate and speed at lactate threshold were determined using the pitch test. The indirect calorimetry method was applied to assess energy expenditure of the run. The training work carried out by the study participant was subject to registration and quantitative as well as qualitative analysis. Results: Observations indicated that the implemented training programme resulted in a reduction of energy expenditure by 6.32% when running at threshold speed. During the 10-km competitive run, the studied athlete obtained an average heart rate and running speed at a level corresponding to 109% and 108% (respectively) of the threshold values for the specified parameters. Conclusions: The proposed training programme had a positive effect on running economics at threshold speed. It was shown that the average heart rate and speed obtained during the competition over a distance of 10 km exceeded the threshold values of the mentioned parameters by 9 and 8%, respectively.